The Influence of the Semantic Material on the Assessment of Speech Reception Threshold - KRENZ, Magdalena; WICHER, Andrzej; SĘK, Aleksander (Archives of Acoustics, 2015)
To determine speech intelligibility using the test suggested by Ozimek et al. (2009), the subject composed sentences with the words presented on a computer screen. However, the number and the type of these words were chosen arbitrarily. The subject was always presented with 18, similarly sounding words. Therefore, the aim of this study was to determine whether the number and the type of alternative words used by Ozimek et al. (2009), had a significant influence on the speech intelligibility. The aim was also to determine an optimal number of alternative words: i.e., the number that did not affect the speech reception threshold (SRT) and not unduly lengthened the duration of the test. The study conducted using a group of 10 subjects with normal hearing showed that an increase in the number of words to choose from 12 to 30 increased the speech intelligibility by about 0.3 dB/6 words. The use of paronyms as alternative words as opposed to random words, leads to an increase in the speech intelligibility by about 0.6 dB, which is equivalent to a decrease in intelligibility by 15 percentage points. Enlarging the number of words to choose from, and switching alternative words to paronyms, led to an increase in response time from approximately 11 to 16 s. It seems that the use of paronyms as alternative words as well as using 12 or 18 words to choose from is the best choice when using the Polish Sentence Test (PST).